Early articular cartilage MRI T2 changes after anterior cruciate ligament reconstruction correlate with later changes in T2 and cartilage thickness. Issue 3 (29th July 2016) - Williams, Ashley; Winalski, Carl S.; Chu, Constance R.
ABSTRACT: Anterior cruciate ligament (ACL) injury is a known risk factor for future development of osteoarthritis (OA). This human clinical study seeks to determine if early changes to cartilage MRI T2 maps between baseline and 6 months following ACL reconstruction (ACLR) are associated with changes to cartilage T2 and cartilage thickness between baseline and 2 years after ACLR. Changes to T2 texture metrics and T2 mean values in medial knee cartilage of 17 human subjects 6 months after ACLR were compared to 2‐year changes in T2 and in cartilage thickness of the same areas. T2 texture and mean assessments were also compared to that of 11 uninjured controls. In ACLR subjects, six‐month changes in mean T2 correlated to 2‐year changes in mean T2 ( R  = 0.80, p  = 0.0001), and 6‐month changes to T2 texture metrics, but not T2 mean, correlated with 2‐year changes in medial femoral cartilage thickness in 9 of the 20 texture features assessed ( R  = 0.48–0.72, p  ≤ 0.05). Both mean T2 and texture differed ( p  < 0.05) between ALCR subjects and uninjured controls.Clinical Significance: These results show that short‐term longitudinal evaluation of T2 map and textural changes may provide early warning of cartilage at risk for progressive degeneration after ACL injury and reconstruction. © 2016 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 35:699–706, 2017.